HISTORY AND LAW ENFORCEMENT REGULATIONS OF THE CRIMINAL ACT OF DEFAMATION AGAINST THE STATE SYMBOL - K.A. Noviansyah; Armi Antasari; K.M. Faisal Reza (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The history of the Indonesian national symbol, Garuda, has been known to the people of the archipelago since the fifth century during the Tarumanegara Kingdom, whose king, Purnawarman, embraced the Hinduism of the Vishnu sect and since then the Garuda symbol has been known in the archipelago. On January 10, 1950, the government of the Republic of Indonesia Serikat (RIS) at that time formed a technical committee called the State Symbol Committee chaired by Mohammad Yamin. which finally the symbol proposed by Sultan Hamid II was Garuda because he was inspired by the majesty of the mythological bird and hoped that Indonesia could also become a strong country. The regulation of law enforcement for criminal acts of desecration of the Garuda national symbol is carried out through criminal liability by fulfilling the elements and applying criminal sanctions for criminal acts of desecration of the national symbol as stipulated in Article 68 of Law Number 24 of 2009 concerning the Flag, Language, and State Symbol, and the National Anthem, where the perpetrators are subject to a maximum imprisonment of 5 (five) years or a maximum fine of Rp. 500,000,000.00 (five hundred million rupiah).